Transformasi Digital dalam Pengelolaan Sumber Daya Manusia: Analisis Dampak Artificial Intelligence terhadap Produktivitas dan Engagement Karyawan di Era Industri 5.0 - Gilang, Gilang; Komariyah, Imas; Sudrajat, yayat (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the impact of the use of Artificial Intelligence (AI) in Human Resources (HR) management on the effectiveness of technology implementation, employee productivity, and the involvement of organizational culture as a moderating variable in the Industry 5.0 era. This study uses a quantitative approach with a path analysis test method on three regression models. Model 1 analysis results show that the use of AI in HR has a significant effect on the effectiveness of technology implementation with a value of F = 35.320 and p < 0.05, and contributes 26.3% to the effectiveness of technology implementation (R² = 0.263). In Model 2, the effectiveness of technology implementation and the use of AI together have a significant effect on employee productivity with a value of F = 27.111, p < 0.05, and a contribution of 35.6% (R² = 0.356). Model 3 shows that organizational culture as a moderating variable is not significant in strengthening the relationship between technology implementation effectiveness and employee productivity (t = 0.180, p = 0.858). However, the R² value of 0.384 indicates that 38.4% of the variation in employee productivity can be explained by the independent and moderating variables in this model. This study concludes that the use of AI in HR significantly improves the effectiveness of technology implementation and employee productivity. However, the role of organizational culture as moderation needs to be further explored as it did not contribute significantly in this model